Polimorfisme Gen Vitamin D Receptor (VDR) BsmI pada Multi Drug Resistant Tuberculosis (MDR TB)" - Sibuea, Christine Verawaty; Pardosi, Maria Oktaviana; Simbolon, Ira Maylani; Tampubolon, Paulus Adventus (Nommensen Journal of Medicine, 2023)
ABSTRACT Background : The increasing cases of Tuberculosis (TB) is a concerned health problem to the world, especially Indonesia, which Indonesia is the 2nd most TB cases in the world. The increase in TB cases is accompanied by the increase in Multi Drug Resistant Tuberculosis (MDR TB) cases. Genetic and immunity host factor, inadequate treatment and bacterial mutations affect the infection of MDR TB. Vitamin D has an important role in immune regulatory to eliminate Mycobacterium tuberculosis, as of it can affect the susceptibility to MDR TB. Purpose : The aim of this study was to determine the polymorphism of the Vitamin D Receptor (VDR) BsmI gene in MDR Tuberculosis. Methods : This study was a case control study involving 32 non-MDR TB patients and 32 MDR TB patients. The VDR gene was restricted by the Restriction Fragment Length Polymorphism (RFLP) method using BsmI enzyme and agarose gel visualization was performed. Results : Homozygous variant GG genotype was found higher in non-MDR Tuberculosis (43.75%) than in MDR Tuberculosis (18.8%), and heterozygotes AG genotype was not found in MDR Tuberculosis either in non MDR Tuberculosis. There was no significant relationship between the VDR BsmI gene polymorphism and MDR tuberculosis (p>0.05). Conclusion : This results showed that BsmI VDR gene polymorphism does not affect the susceptibility to MDR Tuberculosis. Keywords : VDR gene, polymorphism, MDR tuberculosis, non-MDR tuberculosis, RFLP ABSTRAK Latar belakang : Peningkatan kasus Tuberkulosis (TB) merupakan masalah kesehatan yang menjadi perhatian bagi dunia khususnya Indonesia, dimana Indonesia merupakan negara dengan kasus TB terbanyak ke-2 di dunia. Kasus TB yang meningkat disertai juga dengan peningkatan kasus Multi Drug Resistant Tuberculosis (MDR TB). Faktor pejamu genetik dan imunitas, pengobatan yang tidak adekuat dan mutasi bakteri, mempengaruhi terjadinya MDR TB. Vitamin D memiliki peran penting dalam regulasi imunitas tubuh untuk mengeliminasi mycobacterium tuberculosis, sehingga dapat mempengaruhi kerentanan seseorang menderita MDR TB . Tujuan : Penelitian ini bertujuan untuk mengetahui polimorfisme gen Vitamin D Receptor (VDR) BsmI pada MDR Tuberkulosis. Metode : Penelitian ini merupakan penelitian case control yang melibatkan 32 penderita non MDR TB dan 32 penderita MDR TB. Gen VDR direstriksi dengan metode Restriction Fragment Length Polymorphism (RFLP) menggunakan BsmI dan dilakukan visualisasi gel agarose. Hasil : Genotif homozigot varian GG lebih banyak ditemukan pada non MDR Tuberkulosis (43,75%) dibandingkan pada MDR Tuberkulosis (18,8%) dan genotif heterozigot AG tidak terdapat pada semua subjek. Tidak terdapat hubungan yang signifikan antara polimorfisme gen VDR BsmI dengan MDR Tuberkulosis (p>0,05). Kesimpulan : Polimorfisme gen VDR BsmI tidak mempengaruhi kerentanan menderita MDR Tuberkulosis. Kata Kunci : Gen VDR, polimorfisme, MDR Tuberkulosis, Non MDR Tuberkulosis, RFLP